Efeito protetor de CXCL10 em infecção experimental por Leishmania braziliensis - Guerra, Priscila Valera (2013)
Leishmania braziliensis is the more common etiologic agent of the cutaneous leishmaniasis in Brazil. BALB/c mice are more susceptible to L. braziliensis infection, although develop small and not ulcerated lesions. The lesions in BALB/c mice infected by L. braziliensis are accompanied by expression of a broad chemokines spectrum, including CXCL10, which is able to attract and activate NK and Th1 cells with IFN-γ production. The aim of this study was to evaluate whether the chemokine CXCL10, administered in early stages of infection could influence the course of disease, leading to a faster and more effective time of healing. Groups of BALB/c mice (n=24) were infected by L. braziliensis and divided into two groups: one group (n=12) received CXCL10 (100 ng/5μL) and the other (n=12) received PBS (5μL), at 1, 3, 5 and 7 days postinfection. Some parameters were evaluated: thickness of the lesions every three days; parasite burden in both the footpad and the draining lymph node, NO concentration, cytokines production (IFN-γ, IL-12p40, TNF-α, IL-4, IL-10 and TGF-β), at 15 and 30 days after infection; and histopathological analysis of lesions. Animals receiving CXCL10 showed reduced disease duration, since the lesions started to regress earlier (12 days), whereas the control animals developed the disease for longer (15 days). CXCL10 induced statistically significant differences in parasite load in the draining lymph nodes compared with control in both times evaluated (15 days: p=0.0353; 30 days: p=0.0292). In the animals receiving CXCL10 was not observed change in the number of parasites in the site of inoculation, even with reduced thickness of the lesion, showing no correlation between lesion size and parasite load. There was no difference in NO concentration between groups with 15 days of infection, and this concentration remained the same in the group receiving CXCL10 at day 30, although it was lower than that observed in the control group. CXCL10 also induced higher levels of IFN-γ and IL-12, and reduced IL-4, IL-10, and TGF-β at 30 days postinfection, when compared to control animals. Histopathology analyses of lesions after 15 days postinfection showed a very mild inflammation in both groups, differing only for the presence of neutrophils, which were practically not observed in lesions of animals receiving CXCL10. Taken together, the data from this study showed CXCL10 chemokine presented a protective effect on L. braziliensis infection in BALB/c mice, with a reduction in the progression of the disease, associated with a higher concentration of IFN-γ and lesser of IL-4 and IL-10.